1991
DOI: 10.1111/j.1432-1033.1991.tb15942.x
|View full text |Cite
|
Sign up to set email alerts
|

Covalent structure of two novel neutrophile leucocyte‐derived proteins of porcine and human origin

Abstract: The covalent structures of two, novel, neutrophile, leucocyte-derived, strongly basic proteins of porcine and human origin have been determined by microsequencing in combination with time-of-flight plasma desorption mass spectrometry. The porcine protein primary structure of 219 amino acid residues was shown to contain 6 cysteine residues, 2 putative carbohydrate sites and 14% basic residues. The human protein contained 221 amino acid residues of which 8 were cysteine, 4 putative carbohydrate sites and 12% bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 27 publications
2
71
0
Order By: Relevance
“…Based on the human HBP amino acid sequence [3] and the CAP37/ azurocidin cDNA sequence [8,9] a 770 bp BamHI HindlII fragment was constructed by PCR technology by usage of a human bone marrow cDNA library (Clontech). This fragment contains the entire coding region of HBP, including a 19-residue signal peptide, a 7 amino acid pro-peptide, a mature part of 222 amino acids, and a 3 amino acid C-terminal extension.…”
Section: Construction Of Transfer Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the human HBP amino acid sequence [3] and the CAP37/ azurocidin cDNA sequence [8,9] a 770 bp BamHI HindlII fragment was constructed by PCR technology by usage of a human bone marrow cDNA library (Clontech). This fragment contains the entire coding region of HBP, including a 19-residue signal peptide, a 7 amino acid pro-peptide, a mature part of 222 amino acids, and a 3 amino acid C-terminal extension.…”
Section: Construction Of Transfer Vectorsmentioning
confidence: 99%
“…Heparin-binding protein (HBP), also termed CAP37 [1] and azurocidin [2], is a human neutrophil-derived serine protease homologue exhibiting 45% sequence identity to neutrophil elastase, and 30-37% identity to several other granule serine proteases [3,4]. Despite these similarities, HBP is devoid of proteolytic activity because the active site residues serine and histidine have been replaced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat later, Gabay et al [15] characterized a PMN-derived bactericidal protein from the azurophilic granules of human PMN, which they named azurocidin. In parallel, Flodgaard et al [16] isolated a protein from human and porcine PMN that displayed strong binding capability for heparin, earning it the name HBP. Complete sequencing has shown that CAP37, azurocidin, and HBP are the same protein.…”
Section: Azurocidin Is Unique Among the Pmn Granule Proteinsmentioning
confidence: 99%
“…In a newly discovered protein, which is highly similar to hepatocyte growth factor and which possesses putative tumor suppressor properties (Han et al, 1991) all three residues of the triad, including Aspl02, have been mutated. We have recently identified yet another example of such a non-enzymatic, active-site-mutated member of the serine proteinase family (Flodgaard et al, 1991). The protein was characterized by a high affinity for heparin and termed 'heparin binding protein' (HBP).…”
mentioning
confidence: 99%